Study on the theoretical calculation method of jet precooling evaporation of the TBCC engine - Jianyong Zhu; Yuchen Feng; Taiqiu Liu; Xin You (Results in Engineering)
Jet precooling technology is an effective way to solve the thrust trap problem in TBCC engine mode conversion. In practical experiments, the evaporation rate characterizes the cooling effect in the cooling section and is one of the important parameters that need to be obtained. However, high temperature and high humidity environments have a significant impact on the measurement of evaporation rate, and obtaining accurate evaporation values in experiments is one of the difficulties in jet precooling experiments. This study proposes a 0-D theoretical calculation model for calculating the droplet evaporation rate during the jet cooling process based on the law of energy conservation and easily measurable physical property parameters at the inlet and outlet from the perspective of theoretical calculation and verifies it by simulation under 15 typical working conditions. The results show that the proposed 0-D model has a calculation error of less than ±1 % under the given 15 working conditions, indicating that this method can accurately calculate the evaporation rate of the jet cooling process. For a turbine engine flying at a constant dynamic pressure of 46KPa, when Ma=2.5 and the jet flow rate is 4 % of the inlet flow rate, a maximum evaporation rate of 100 % can cause a 20.5 % increase in the temperature drop coefficient of the turbine engine. The equivalent Mach number at the outlet of the precooling section of the engine without precooling decreases by 0.42, effectively improving the upper limit of the turbine engine's operation.